PANDANGAN HUKUM ISLAM TERHADAP DEMOKRASI PEMILIHAN KEPALA DESA - Mu’in, Fathul (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2019)
The village heads election is one of the popular democratic parties. This moment becomes an arena of political competition to become a leader or want to participate in a higher democratic party, such as legislative elections, elections for regents, governors, and presidential elections. However, this village-level democracy party often experiences problems. The practice of fraud, the use of ethnic, racial, and money politics issues so that the democratic party turns into a power struggle, which also makes fraternity and village development stagnant. The purpose of this study was to determine the views of Islamic law on the democratic process of village head elections. The results of this study conclude, theoretically the village head election democracy has gone quite well, but its application has not been fully implemented. Like the existence of behavior that is not in accordance with Islamic values and the principles of a democratic country, namely the existence of money politics. Most people consider money politics as a seasonal fortune. Islamic law views, democracy and shura are not two different things but they must not be contested. Direct election democracy can be a part of the political system of Muslims if the orientation and value system are loaded with religious values and morality rather than justifying any means and transaction of office.